Anti-cancer and cardioprotective effects of indol-3-carbinol in doxorubicin-treated mice. Issue 1 (January 2016) - Adwas, Almokhtar A.; Elkhoely, Abeer A.; Kabel, Ahmed M.; Abdel-Rahman, Mohamed Nabih; Eissa, Amany A.
Abstract: Doxorubicin (DOX) is a broad-spectrum antitumor antibiotic used in treatment of cancer. Its effect may be complicated by increased risk of cardiotoxicity. It was suggested that natural compounds with anticancer properties can be used in combination with DOX to decrease its dose and side effects. Indole-3-carbinol (I3C) is one of the phytochemicals that was shown to have anti-cancer effect. Our aim was to detect the possible chemosensitizing effects of I3C in DOX-induced cytotoxicity and the possible cardioprotective effects of I3C in DOX-induced cardiotoxicity. One hundred mice were divided into five equal groups: Control untreated group, solid Ehrlich carcinoma (SEC), SEC + DOX, SEC + I3C, SEC + DOX + I3C. Tumor volume, serum creatinine kinase and lactate dehydrogenase were measured. Also, tissue malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), sphingosine kinase-1 (SphK1) activity and interleukin-6 (IL-6) were determined. Parts of the tumor and cardiac tissues were subjected to histopathological examination. DOX or I3C alone or in combination induced significant increase in tumor CAT and SOD with significant decrease in tumor volume, tumor MDA, SphK1 activity and IL-6 and alleviated the histopathological changes with significant increase in the apoptotic index and significant decrease in tissue bcl2 compared to SEC group. Also, DOX induced cardiotoxicity which was ameliorated by I3C. In conclusion, DOX/I3C combination had a better effect than each of DOX or I3C alone against SEC in mice with marked improvement of the cardiotoxicity induced by DOX.